2010
DOI: 10.1016/j.enbuild.2009.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between standards and the lifetime commissioning

Abstract: This paper reviews the applicability and drawbacks of available European and international standards related to lifetime commissioning, by structuring them into Norwegian commissioning procedures. The work describes research on lifetime commissioning that proposes a generic framework on building performances. The generic framework describes a component in HVAC system by performances. The results of the standard review show that there is a need for measurement and testing standards in hydronic systems. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The method has been reported in [8]. The aim of the procedures is to create a good information system between all the participants during the building lifetime.…”
Section: Norwegian Ltc Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The method has been reported in [8]. The aim of the procedures is to create a good information system between all the participants during the building lifetime.…”
Section: Norwegian Ltc Proceduresmentioning
confidence: 99%
“…This framework describes building performance as a data model [8]. In our study, a generic framework on building performance is suggested.…”
Section: Norwegian Ltc Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…This standard concerns the impact of the BACS and the TBM on energy performance and energy use in buildings. There are four BACS efficiency classes described in this document: (i) the class A corresponds to the BACS with very high impact on energy consumption, (ii) the class B-the BACS with high impact on energy use, (iii) the class C-the BACS with low impact on energy consumption and (iv) class D-the BACS without any impact on the energy consumption in buildings (Djuric and Novakovic 2010;Schönenberger 2015). Considering this, and taking into account the assumptions for the classes as well as the functions available in the street lighting control system, in our experiment, we propose four different functional strategies (EN 15232 Standard 2012):…”
Section: Implementation and Verification Of Control Scenariosmentioning
confidence: 99%